Google, the Medium, and Hermeneutic Principles. - Finger, Anke K. (Contemporary French & Francophone Studies, 2019)
Google's role in curating the Internet, is, conceptually, a simple one. It offers speed and knowledge infrastructures of unfathomable size. It is a medium, a filter, through which you, the inquirer, meets information or data provided by other users. What has been more difficult to understand and grapple with, over the twenty-one years since Google Search has existed as an information consolidator, is a) its role as a multimodal digital medium for the user's approach to knowledge design, and b) its media identity as the giant of information consolidation and dispensation, that, based on its famously secret algorithm, supports a business model focused on advertising. In this article, I join a number of media studies and digital culture experts, who warn that we should first begin to understand the Internet before we employ Blockchain technology for Web 3.0 purposes. In order to utilize Google as informed consumers, we need to understand not only what it is as a medium, but also how we as consumers co-create the Googlesphere by both designing and accessing knowledge. For while the mission of Google describes what sounds like a democratic model, the hermeneutics of "organize," "world's information," "universally accessible," and "useful" point to semantic categories with considerable potential for bias, exploitation, or abuse when applied to an advertising enterprise.